Integrasi Luas Permukaan Bangun Ruang dan Design Thinking dalam Proyek Paving Block Ramah Lingkungan - Rohma, Hanifah Nur; Susanto, Susanto; Firmansyah, Frenza Fairuz (Pendidikan Matematika FKIP Universitas Mataram, 2025)
As part of the community environment, the school faces challenges in managing the growing amount of plastic waste. Through a project of making paving blocks from plastic waste, this study aims to help students learn geometry by integrating the concept of surface area of 3D shapes into real-life practice. Students took part in the project by designing and creating hexagonal prism-shaped paving blocks to cover the archery extracurricular area, which often gets muddy during rainy days. This study was conducted using a descriptive qualitative approach. Interviews with students and teachers, project process documentation, and observation of learning activities were all methods used to collect data. The results show that the Design Thinking approach supported students in understanding surface area in a more practical way, especially in calculating the dimensions and quantity of paving blocks needed. The project also encouraged students to be more aware of environmental issues.